Observations of canopy storage capacity and wet canopy evaporation in a humid boreal forest - Hadiwijaya, Bram; Isabelle, Pierre‐Erik; Nadeau, Daniel F.; Pepin, Steeve (Hydrological processes, 2021)
Evaporation of intercepted rain by a canopy is an important component of evapotranspiration, particularly in the humid boreal forest, which is subject to frequent precipitation and where conifers have a large surface water storage capacity. Unfortunately, our knowledge of interception processes for this type of environment is limited by the many challenges associated with experimental monitoring of the canopy water balance. The objective of this study is to observe and estimate canopy storage capacity and wet canopy evaporation at the sub‐daily and seasonal time scales in a humid boreal forest. This study relies on field‐based estimates of rainfall interception and evapotranspiration partitioning at the Montmorency Forest, Québec, Canada (mean annual precipitation: 1600 mm, mean annual evapotranspiration: 550 mm), in two balsam fir‐white birch forest stands. Evapotranspiration was monitored using eddy covariance sensors and sap flow systems, whereas rainfall interception was measured using 12 sets of throughfall and six stemflow collectors randomly placed inside six 400‐m2 plots. Changes in the amount of water stored on the canopy were also directly monitored using the stem compression method. The amount of water intercepted by the forest canopy was 11 ± 5% of the total rainfall during the snow‐free (5 July–18 October) measurement periods of 2017 and 2018. The maximum canopy storage estimated from rainfall interception measurements was on average 1.6 ± 0.7 mm, though a higher value was found using the stem compression method (2.2 ± 1.6 mm). Taking the average of the two forest stands studied, evaporation of intercepted water represented 21 ± 8% of evapotranspiration, while the contribution of transpiration and understory evapotranspiration was 36 ± 9% and 18 ± 8%. The observations of each of the evapotranspiration terms underestimated the total evapotranspiration observed, so that 26 ± 12% of it was not attributed. These results highlight the importance to account for the evaporation of rain intercepted by humid boreal forests in hydrological models. Measurements of canopy water balance components are performed in a humid balsam fir boreal forest during the snow‐free seasons of 2017 and 2018. The rate of change in water volume on the canopy was estimated with water balance and directly measured using stem compression system. Evapotranspiration partitioning was estimated with eddy‐covariance and sapflow measurements.